2014
DOI: 10.1007/s11306-014-0672-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic consequences of LDHA inhibition by epigallocatechin gallate and oxamate in MIA PaCa-2 pancreatic cancer cells

Abstract: Lactate dehydrogenase A (LDHA) is the enzyme that converts pyruvate to lactate and oxidizes the reduced form of nicotinamide adenine dinucleotide (NADH) to NAD+. Several human cancers including the pancreas display elevated expression of LDHA. Because of its essential role in cancer metabolism, LDHA has been considered to be a potential target for cancer therapy. Recently, we have shown that a green tea extract significantly down-regulated LDHA in HPAF-II pancreatic cancer cells using global proteomics profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 37 publications
2
37
0
1
Order By: Relevance
“…Many studies in tumors confirms the view that target LDHA may represent novel therapeutic strategies for controlling tumor growth [9,10,12,[15][16][17] . Meanwhile, previous reports showed that the expression of LDHA was abnormality abundant in RCC than that in matched normal renal tissue [2,20] , which promotes us to determine the function of LDHA on renal cancer development.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Many studies in tumors confirms the view that target LDHA may represent novel therapeutic strategies for controlling tumor growth [9,10,12,[15][16][17] . Meanwhile, previous reports showed that the expression of LDHA was abnormality abundant in RCC than that in matched normal renal tissue [2,20] , which promotes us to determine the function of LDHA on renal cancer development.…”
Section: Discussionmentioning
confidence: 83%
“…Lactate dehydrogenase A (LDHA) catalyzes the final step of glycolysis in which pyruvate is directly converted to lactate, indicating the critical role for maintaining glycolysis in tumorigenesis [14] . It has been reported that the expression of LDHA is abnormal in many human cancers, such as prostate cancer [15] , ovarian cancer [16] , pancreatic cancer [17,18] and breast cancer [19] . Meanwhile, inhibition of LDHA reduced several tumor progression [14][15][16][17] , indicating the underlying role of LDHA as a promising target for cancer therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, inhibition of glycogenolysis by glycogen phosphorylase inhibitor (CP-320626) resulted in significant reduction in both oxidative and non-oxidative pentose cycle activities, and decreased pyruvate dehydrogenase activity and de novo lipogenesis in pancreatic cancer MIA PaCa-2 cells apoptosis (Lee et al, 2004). Similar metabolic changes in pentose cycle and de novo lipogenesis were observed when lactic acid production was inhibited by oxamate, a lactic acid dehydrogenase (LDHA) inhibitor (Lu et al, 2014). Inhibition of signaling pathways also can impact on cancer cell metabolism and growth.…”
Section: Introductionmentioning
confidence: 74%
“…In a recent study of the effect of oxamate on the Warburg phenotype (Lu et al, 2014), it was observed that inhibition of LDHA had upstream and downstream metabolic consequences suggesting the possibility of three functional compartments, namely i) glycolytic/pentose cycle, ii) lactate/pyruvate and iii) mitochondrial/TCA compartments. These three functional compartments within the metabolic system are also suggested by the observations in the “glucose paradox” (Katz and McGarry, 1984).…”
Section: Balance Of Flux In Systems Biologymentioning
confidence: 99%